[East Indian woman, Trinidad, B.W.I.] - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, 15 Frederick Street, Port of Spain, Trinidad ; Made in Germany, 2008)
Photo of an East Indian woman in traditional wear, including a nose ring, necklaces and bracelets.
Colour: Brown and White; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; Trinidad and Tobago; Women, East Indian--Trinidad and Tobago; East Indians--Trinidad and Tobago; Ethnic costume--India; Jewelry--India; Bracelets--India; Nose rings--India; Necklaces--India